Teaching genre exploring 9 types of literature to develop lifelong readers and writers - McCarthy, Tara (New York Scholastic Professional Books, 1996)
Teaching activities and reproducible pages on nine genres or subgenres of literature: poetry, biography, autobiography, reports of information, realistic fiction in a modern setting, historical fiction, folk literature, mystery, modern fantasy and science fiction.
"Grades 4-8"--Cover.
Keywords: Literature -- Study and teaching (Elementary); Reader-response criticism; Literary form -- Study and teaching (Elementary); Fiction genres -- Study and teaching (Elementary)